A method to measure clinical practice patterns of breast cancer genomic diagnostics in health systems. (August 2012) - Atehortua, Nelson A; Issa, Amalia M
Personalized genomic diagnostics, often in combination with targeted therapeutics, have become an important component of clinical oncologic practice over the last decade. However, there is a dearth of studies examining utilization of specific genomic diagnostics and their influence on clinical practice patterns in health systems. In order to begin to explore and understand the clinical utility of particular genomic diagnostics in current use, we developed an instrument to collect data on utilization and clinical practice patterns in health systems. We focused our efforts on gene-expression profiling (GEP) assays, particularly on a commonly used GEP in breast cancer: Oncotype DX ® (Genomic Health, Inc., CA, USA). This article presents a method we have developed for the retrospective collection of data on the utilization of GEP among breast cancer patients of a real-world, real-time health system.